Levirate Obligation and Widowhood in Dialogue: Deuteronomy 25:5–10 and Contemporary Practices in Amike Aba, Nigeria - Uroko, Favour Chukwuemeka; Emerionwu, Michael (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2025)
This study examines the relationship between levirate obligation in Deuteronomy 25:5–10 and lived widowhood practices in Amike Aba (Izzi, Ebonyi State, Nigeria), where mourning rites, kin authority, and land-based inheritance shape widows’ post-bereavement security. Using a qualitative design that integrates textual analysis and field inquiry, the research conducts a close reading of Deuteronomy 25:5–10 (its casuistic structure, conditions, actors, purposes, and refusal procedure). It analyses primary interview data from 25 participants (17 widows and eight male community members) through thematic analysis. The findings indicate that the biblical text frames levirate as a kin-based obligation aimed at name/estate continuity, coordinated through the widow–levir–elders triad and regulated by a public refusal procedure marked by supervised shame. Field accounts show that widowhood in Amike Aba is organised through a sequenced ritual regime (public wailing, visible status markers such as hair shaving and mourning attire, selective restrictions of movement, and reintegration tied to second burial), which intersects with post-bereavement vulnerabilities including exclusion from decision-making, insecurity around land/inheritance, exposure to harassment, and stigma surrounding remarriage. The study’s implications highlight the need for context-sensitive community practices and local safeguarding mechanisms that mitigate prolonged liminality resulting from delayed ritual closure, enhance widows’ access to use rights and mediation in inheritance processes, and reduce exposure to harassment and stigma. The originality of this study lies in bringing the normative–procedural logic of Deuteronomy’s levirate law into a sustained dialogue with a micro-contextual ethnographic account of Amike Aba, showing how kin obligation can function as both social protection and social regulation, thereby clarifying why “choice” may exist yet remain materially and relationally constrained.